2014
DOI: 10.1111/jdv.12784
|View full text |Cite
|
Sign up to set email alerts
|

Adult eczema in Italy: prevalence and associations with environmental factors

Abstract: Eczema and EAH are highly prevalent in Italian young adults, especially in women. Our results suggest that adult onset is not unusual, and that environmental factors may influence the occurrence of eczema and EAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
56
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 31 publications
9
56
1
5
Order By: Relevance
“…We found in the present study an overall point prevalence of AD of 4.65%, which corresponds to 4.652 patients per 100.000 persons in France with women being twice often more affected than men. In an Italian national multicentre population‐based study, the authors reported an 8.1% prevalence of eczema in Italian young adults . Consistently, a large population‐based survey conducted in the United States reported a 12‐month prevalence of adult eczema of 10.2% .…”
Section: Discussionmentioning
confidence: 64%
“…We found in the present study an overall point prevalence of AD of 4.65%, which corresponds to 4.652 patients per 100.000 persons in France with women being twice often more affected than men. In an Italian national multicentre population‐based study, the authors reported an 8.1% prevalence of eczema in Italian young adults . Consistently, a large population‐based survey conducted in the United States reported a 12‐month prevalence of adult eczema of 10.2% .…”
Section: Discussionmentioning
confidence: 64%
“…30 Particulate matter is a complex mixture of liquid and solid droplets suspended in gas which comprises sulphates, nitrates, carbon compounds, various types of dust, biological contaminants and gaseous contaminants. [37][38][39] Consequently, PM 10 , SO 2 and NO 2 have acute influence on eczema outpatients. 31,32 Oxidative stress via excessive ROS production by particulate matter exposure increases pro-inflammatory cytokines, such as TNF-a and IL-8, and MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Adults with moderate-to-severe AD have been shown to have poorer health status, 1 sleep disturbances, 1 higher rates of fractures and other injuries, 4 obesity and other cardiovascular disease risk factors, 5,6 and depression and other mental health comorbidities. 7 The mainstays of treatment for AD are emol-lients, topical corticosteroids, calcineurin inhibitors and avoidance of exacerbants.…”
Section: Original Article P 1621mentioning
confidence: 99%
“…3 Identifying topical antiseptics that could be used effectively during surgery to irrigate the debulked surgical field to kill viable organisms without leading to local tissue damage in a time frame that could be practically adopted during a clinical procedure is tantalizing. Understanding not only the fungicidal potential of the agents but also the time to kill to assess if this will be of practical use has been addressed in this work.…”
Section: Original Article P 1657mentioning
confidence: 99%
See 1 more Smart Citation